MEKANISME PEMBIAYAAN PADA PRODUKSI GULA KELAPA DI KECAMATAN ILIR TALO KABUPATEN SELUMA (Studi Terhadap Pelaksanaan dan Pengembangan Produsen Gula Kelapa) - Isnaini, Desi (Institut Agama Islam Bengkulu, 2016)
This paper represents a financing mechanism that uses mudaraba and qardh contracts. The writing of this paper is motivated from academic anxiety in looking at the financing mechanism in the existing economic system in Ilir Talo district Seluma district on the aspect of the system of financing the production of palm sugar. In his discussion discusses the meaning of Baitul Maal Wattamwil (BMT) as well as the stages of its establishment, mudaraba and qardh, mudharabah and qardh financing schemes, financing calculation system using mudharabah and qardh contracts and appropriate financing analsis to solve the problems of economic system in sub district Ilir Talo Seluma district. And concluded that the appropriate financing system for the state of the existing economic system in the district Ilir Talo Seluma district with the qardhul hasan contract. And provide recommendations to establish a sharia financial institution in the form of BMT as the savior of the community economy.Keyword: BMT, Mudharabah, Qardh, Ilir Talo District